Outcomes of preoperative radiotherapy and resection of retroperitoneal sarcoma. (3rd September 2012) - Alford, Simone; Choong, Peter; Chander, Sarat; Henderson, Michael; Powell, Gerard; Ngan, Samuel
Abstract Background Preoperative radiotherapy (RT) is an important component of the management of retroperitoneal sarcoma (RPS). We aimed to establish the feasibility of this approach by determining the accuracy of computed tomography (CT)‐guided core biopsy, proportion of patients completing treatment, rates of acute toxicity and surgical complications, and treatment outcomes. Methods This is a retrospective review. Consecutive patients presenting between January 1999 and December 2009 with a diagnosis of either primary or recurrent RPS were identified. Those patients suitable for preoperative RT and surgery were included. Exclusions included presence of metastatic disease, age under 18 years and/or paediatric histology, and treatment with palliative intent. Results Twenty‐four patients were included, 14 were males. Median age was 61.4 years. Twenty‐three patients had Stage T2b, high‐grade disease. Twenty patients were treated at initial presentation and four at first local recurrence. Five‐year progression‐free survival, overall survival and local recurrence rates were 48.9, 53.7 and 22%, respectively. A malignant diagnosis was confirmed in all patients who underwent CT‐guided core biopsy; a diagnosis of sarcoma was reached in 90%, histological subtype correctly identified in 66%. All patients in the cohort completed preoperative RT. Grade 3 toxicity occurred in 4% of patients (n = 1). Seventy‐five per cent (n = 18) proceeded to radical resection, where complete macroscopic excision was achieved in all cases. There was no perioperative mortality. Conclusion Preoperative RT has low levels of Grades 3 or 4 toxicity, and does not adversely impact surgical management. CT‐guided core biopsy is an accurate means of confirming a diagnosis of RPS prior to definitive treatment.